Microvessels derived from hiPSCs are a novel source for angiogenesis and tissue regeneration. (December 2022) - Gao, Xin; Ma, Shixing; Xing, Xiaotao; Yang, Jian; Xu, Xun; Liang, Cheng; Yu, Yejia; Liu, Lei; Liao, Li; Tian, Weidong
The establishment of effective vascularization represents a key challenge in regenerative medicine. Adequate sources of vascular cells and intact vessel fragments have not yet been explored. We herein examined the potential application of microvessels induced from hiPSCs for rapid angiogenesis and tissue regeneration. Microvessels were generated from human pluripotent stem cells (iMVs) under a defined induction protocol and compared with human adipose tissue-derived microvessels (ad-MVs) to illustrate the similarity and differences of the alternative source. Then, the therapeutic effect of iMVs was detected by transplantation in vivo. The renal ischemia-reperfusion model and skin damage model were applied to explore the potential effect of vascular cells derived from iMVs (iMVs-VCs). Besides, the subcutaneous transplantation model and muscle injury model were established to explore the ability of iMVs for angiogenesis and tissue regeneration. The results revealed that iMVs had remarkable similarities to natural blood vessels in structure and cellular composition, and were potent for vascular formation and self-organization. The infusion of iMVs-VCs promoted tissue repair in the renal and skin damage model through direct contribution to the reconstruction of blood vessels and modulation of the immune microenvironment. Moreover, the transplantation of intact iMVs could form a massive perfused blood vessel and promote muscle regeneration at the early stage. The infusion of iMVs-VCs could facilitate the reconstruction and regeneration of blood vessels and modulation of the immune microenvironment to restore structures and functions of damaged tissues. Meanwhile, the intact iMVs could rapidly form perfused vessels and promote muscle regeneration. With the advantages of abundant sources and high angiogenesis potency, iMVs could be a candidate source for vascularization units for regenerative medicine.